Starch modification techniques: an overview - Kaur, Jaspreet; Ahmed, Naseer; Thagunna, Bishal; Kumar, Krishan; Sheikh, Imran; Sharma, Akashdeep (Journal of Postharvest Technology, 2022)
As technologies and processes increase the use of residues, starchy vegetal biomass is becoming an important alternative material in many applications because of its versatility, low cost, and ease of use when altered in its physicochemical properties. A growing number of industrial applications and renewable energy sources employ starch. Several ways have been devised to manufacture a variety of modified starches with various properties and applications. Physically modified starches can be created without chemicals or even biological agents, making them easy and affordable to utilize. Contrarily, starches include many hydroxyl groups that have been used for over a century to create starch esters and ethers as well as other more subtle adjustments, such as adjusting the structure of starches for particular purposes, it is possible to modify them chemically. Thus, the purpose of this review is to summarize recent developments and advances in starch modification. This study discusses enzymatic modification, dual modification, and physical modification techniques. The degree of change in starch characteristics reveals a starch’s resistance or susceptibility to certain chemical changes. By carefully choosing an appropriate modifying agent and a native starch supply, modified starches with desired characteristics and levels of substitution can be created.